Global politics - Heywood, Andrew (Houndmills, Basingstoke, Hampshire, [England] Palgrave Macmillan, 2011)
"This book is a major new introduction to international relations/global politics. Written by a leading textbook author, it is engaging, stimulating and forward-looking, covering all the topics and theory students require at an introductory level"--Provided by publisher.
Includes bibliographical references (pages 524-540) and index.
Keywords: International relations; World politics